¿Terão certos teónimos paleo-hispânicos sido alvo de interpretações (pseudo-)etimológicas durante a romanidade passíveis de se reflectirem nos respectivos cultos? (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
“He who knows names knows also the things” (Plat., Crat., 435d). This ‘cratylist’ presupposition underpins the Orphic thought and later will influence the Stoic philosophy as well. The essential difference is that the Porticus refuses to ontologically enmesh the being of the name with the being of the designated thing; it postulates instead that the name is restricted to mirror the essence of what it designates. Orphism and specially Stoicism, they both play a relevant role in the intellectual education of roman elites. Therefore, it is important to think about the possibility of a ‘cratylist’ approach related to the religious interpretatio processes. In certain circumstances, these processes were done by individuals from those elites in relation to indigenous gods worshiped in western provinces. These indigenous gods are now integrated in the extensive and open pantheon of Romanity. The A. will develop as a case study Endovellicus/Endovollicus’ example.
Keywords: “Cratylisms”; Stoicism; Cultural elites; Interpretatio romana; Endovellicus/Endovollicus